Solar drying in Africa : proceedings of a workshop held in Dakar, Senegal 21-24 July 1986 - Bassey, Michael W., ed. (IRDC OttawaCA, 1987)
Proceedings of workshop on solar drying in Africa attended by 24 participants involved with solar drying research relevant to the continent. 17 papers describe research activities on socio-economic aspects, design and testing of solar dryers, and future research needs. Outlines summary of discussions held during the workshop to assess the state of the art of solar drying research, focusing on progress made and on possible research and collaborative activities that are needed to overcome the technical and socio-economic problems that limit the development and introduction of improved solar dryers.